HUBUNGAN HUKUM KEMITRAAN DALAM LINKAGE PROGRAM PERBANKAN SYARI’AH - Johan Arifin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
Linkage program is a strategy that aims to empower and provide access to capital for small and medium enterprises (UMKM) through the involvement of participation in the financial industry. It is based on the fact that BPR/S or Shari'ah microfinance institutions like Baitul Maal Wa Tamwil (BMT) sometimes have problems in mobilizing public sector funds. While commercial banks on the other hand tend to have excess funds that the public sector (over liquidity) but space is limited to micro business reach its movement.In other words, that the benefits of this program, commercial banks have easy access to UMKM and BMT benefit from the availability of funds to be distributed to the debtor, with due regard to the risk management process so as not to encourage an increase in the ratio of financing problems (non-performing financing).